SOCIAL ECONOMIC LAW AS A TOOL FOR SOCIAL TRANSFORMATION: A LITERATURE REVIEW AND POLICY RECOMMENDATIONS - Loso Judijanto; Melyana R Pugu (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Social economic law is an important instrument in realising social transformation towards a more just and prosperous society. This research aims to examine the potential of social economic law as a tool for social change through a literature study and formulate policy recommendations to optimise its application. The method used is literature. The results show that social economy law has the capacity to encourage wealth redistribution, equal access to economic resources, and protection of the rights of workers and marginalised groups. However, the effectiveness of its implementation is affected by factors such as the quality of legislation, institutional capacity, and support from stakeholders. The proposed policy recommendations include strengthening the legal framework that supports social economy principles, improving institutional capacity, and collaboration between the government, private sector, and civil society in policy implementation. By implementing these recommendations, social economy law can be an effective tool in transforming society towards more equitable justice and prosperity.